A Sweetpotato Auxin Response Factor Gene (IbARF5) Is Involved in Carotenoid Biosynthesis and Salt and Drought Tolerance in Transgenic Arabidopsis - Kang, Chen; He, Shaozhen; Zhai, Hong; Li, Ruijie; Zhao, Ning; Liu, Qingchang (Frontiers in Plant Science, 2018)
Auxin response factors (ARFs) compose a family of transcription factors and have been found to play major roles in the process of plant growth and development. However, their roles in plant carotenoid biosynthesis and responses to abiotic stresses are rarely known to date. In the present study, we found that the IbARF5 gene from sweetpotato (Ipomoea batatas (L.) Lam.) line HVB-3 increased the contents of carotenoids and enhanced the tolerance to salt and drought in transgenic Arabidopsis. The transgenic Arabidopsis plants exhibited the increased abscisic acid (ABA) and proline contents and superoxide dismutase (SOD) activity and the decreased H2O2 content. Furthermore, it was found that IbARF5 positively regulated the genes associated with carotenoid and ABA biosynthesis and abiotic stress responses. These results suggest that IbARF5 is involved in carotenoid biosynthesis and salt and drought tolerance in transgenic Arabidopsis. This study provides a novel ARF gene for improving carotenoid contents and salt and drought tolerance of sweetpotato and other plants.